Kemampuan berpikir kritis dan komunikasi matematis siswa SMP dalam pembelajaran problem posing berbasis kearifan lokal Kalimantan Selatan - Fahriza Noor; Mayang Gadih Ranti (STKIP PGRI Banjarmasin, 2018)
The purpose of this study was to determine students 'critical thinking skills and students' mathematical communication in problem posing learning based on South Kalimantan's local wisdom. This research method is pretest and posttest two group design. The sample in this study were 7A and 7B classes at Banjarbaru 1 Junior High School. Data collection was carried out using test instruments. Data analysis is done descriptively and inferential statistics. The results indicate (1) there is no effect of problem posing learning based on the local wisdom of South Kalimantan on students' critical thinking skills; (2) there is no effect of learning based on South Kalimantan's local wisdom on students' mathematical communication skills; (3) descriptively, problem posing learning based on South Kalimantan's local wisdom is better than conventional learning in critical thinking skills and students' mathematical communication.